2016
DOI: 10.1377/hlthaff.2015.0995
|View full text |Cite
|
Sign up to set email alerts
|

Retail Clinic Visits For Low-Acuity Conditions Increase Utilization And Spending

Abstract: Retail clinics have been viewed by policy makers and insurers as a mechanism to decrease health care spending, by substituting less expensive clinic visits for more expensive emergency department or physician office visits. However, retail clinics may actually increase spending if they drive new health care utilization. To assess whether retail clinic visits represent new utilization or a substitute for more expensive care, we used insurance claims data from Aetna for the period 2010-12 to track utilization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 37 publications
(27 reference statements)
0
39
1
Order By: Relevance
“…Additionally, claims do not provide sufficient information to determine if virtual visits were used in situations when individuals would have otherwise waited to see if the problem resolved on its own. A recent study suggested that RHCs increased utilization for low-acuity visits due to their lower price or convenience [19]. However, whether this is good or bad is a matter of perspective, since while costs may increase, the alternative care options may allow patients who may not have otherwise received appropriate care to receive the care they needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, claims do not provide sufficient information to determine if virtual visits were used in situations when individuals would have otherwise waited to see if the problem resolved on its own. A recent study suggested that RHCs increased utilization for low-acuity visits due to their lower price or convenience [19]. However, whether this is good or bad is a matter of perspective, since while costs may increase, the alternative care options may allow patients who may not have otherwise received appropriate care to receive the care they needed.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual care is also understood as a means of making care more convenient to patients and is gaining momentum in the United States and other advanced health systems alongside other innovations such as retail clinics and other forms of walk-in care [15-20]. There is, at present, limited empirical evidence about how patients view virtual care and more specifically virtual visits, how such care affects overall primary care use, and whether integration of virtual visits in existing relationships or more as a “walk-in” service matters.…”
Section: Introductionmentioning
confidence: 99%
“…About one in five urgent care center users said they chose their provider because the location was “more convenient, compared to other facilities like hospitals, doctors’ offices and community health centers.” Locating primary care clinics in convenient sites might likewise lure patients with nonemergency conditions away from expensive and less convenient emergency departments . Ironically, however, a study of pharmacy‐based retail clinics “found that 58 percent of retail clinic visits for low‐acuity conditions represented new utilization and that retail clinic use was associated with a modest increase in spending, of $14 per person per year.” Accordingly, commentators wonder whether other convenient, lower‐priced options such as “telehealth” or kiosks offering testing in stores “could also end up leading to overall increases in health spending, despite being touted as cost‐savers.” • Every U.S. state has a vaccination mandate but also has procedures for exempting individuals on medical, religious, or philosophical grounds. Several authors have proposed “making [nonmedical] exemptions for immunizations more difficult to obtain.” Their idea is to make the legal procedure for obtaining exemptions more “arduous” by, for instance, requiring “a notarized parental statement, counseling, and health department approval,” as some states do.…”
Section: Articlesmentioning
confidence: 99%
“…12 Ironically, however, a study of pharmacy-based retail clinics "found that 58 percent of retail clinic visits for low-acuity conditions represented new utilization and that retail clinic use was associated with a modest increase in spending, of $14 per person per year." 13 Accordingly, commentators wonder whether other convenient, lower-priced options such as "telehealth" or kiosks offering testing in stores "could also end up leading to overall increases in health spending, despite being touted as cost-savers." 14…”
mentioning
confidence: 99%